Drought‐induced saltwater incursion leads to increased wetland nitrogen export. (13th August 2013) - Ardón, Marcelo; Morse, Jennifer L.; Colman, Benjamin P.; Bernhardt, Emily S.
Abstract: Coastal wetlands have the capacity to retain and denitrify large quantities of reactive nitrogen (N), making them important in attenuating increased anthropogenic N flux to coastal ecosystems. The ability of coastal wetlands to retain and transform N is being reduced by wetland losses resulting from land development. Nitrogen retention in coastal wetlands is further threatened by the increasing frequency and spatial extent of saltwater inundation in historically freshwater ecosystems, due to the combined effects of dredging, declining river discharge to coastal areas due to human water use, increased drought frequency, and accelerating sea‐level rise. Because saltwater incursion may affect N cycling through multiple mechanisms, the impacts of salinization on coastal freshwater wetland N retention and transformation are not well understood. Here, we show that repeated annual saltwater incursion during late summer droughts in the coastal plain of North Carolina changed N export from organic to inorganic forms and led to a doubling of annual NH4 + export from a 440 hectare former agricultural field undergoing wetland restoration. Soil solution NH4 + concentrations in two mature wetlands also increased with salinization, but the magnitude of increase was smaller than that in the former agricultural field. Long‐term saltwater exposure experiments with intact soil columns demonstrated that much of the increase in reactive N released could be explained by exchange of salt cations with sediment NH4 + . Using these findings together with the predicted flooding of 1661 km 2 of wetlands along the NC coast by 2100, we estimate that saltwater incursion into these coastal areas could release up to 18 077 Mg N, or approximately half the annual NH4 + flux of the Mississippi River. Our results suggest that saltwater incursion into coastal freshwater wetlands globally could lead to increased N loading to sensitive coastal waters.